Ekosistem SDM dan Inovasi Ekonomi Digital di Indonesia - Salistia, Faisal; Riyanto, Riyanto; Junaedi, Dedi; Amalia, Rika Sri (MES Bogor, 2023)
The purpose of this study is to analyze the efforts to develop the HR and innovation ecosystem in the digital economy. The research method used is a qualitative analysis method with a litteature study approach. In general, the condition of human resources and digital economy innovation (startup) in Indonesia is still minimal. The lack of human resources makes national digital business actors